2015
DOI: 10.5796/electrochemistry.83.889
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analyses of Amorphous MoS<sub>3</sub> Active Materials in All-solid-state Lithium Batteries

Abstract: We have successfully prepared amorphous MoS 3 (a-MoS 3 ) by ball milling a mixture of Mo metal and sulfur and investigated structural changes during the charge-discharge processes. The XPS measurements revealed that a-MoS 3 should consist of Mo 4+ , S 2 2− , and S 2− . In the XRD profiles of the a-MoS 3 electrodes after the initial discharge and charge tests, only the halo patterns due to the amorphous state were observed without crystalline diffraction peaks. The HR-TEM observations of a-MoS 3 electrodes duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The other doublet with higher binding energies (164.9 eV and 163.1 eV) can be attributed to the bridging S 2 2and/or apical S 2ligands[12,16,19,28]. All these results are similar to those of known MoS 3 samples[19,22,27], but significantly different from those of MoS 2 and other molybdenum sulfide species[27,29,30]. Thus, the obtained molybdenum sulfide material can beassigned as MoS 3 .…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The other doublet with higher binding energies (164.9 eV and 163.1 eV) can be attributed to the bridging S 2 2and/or apical S 2ligands[12,16,19,28]. All these results are similar to those of known MoS 3 samples[19,22,27], but significantly different from those of MoS 2 and other molybdenum sulfide species[27,29,30]. Thus, the obtained molybdenum sulfide material can beassigned as MoS 3 .…”
mentioning
confidence: 66%
“…, a characteristic doublet of Mo 3d 5/2 and Mo 3d 3/2 can be obviously observed at 230.1 and 233.2 eV, respectively, which are typical values for Mo 4+ in MoS 3 or MoS 2[12,16,27]. In addition, the contribution of S 2s at a binding energy of 227.5 eV is clearly noticeable.…”
mentioning
confidence: 79%
“…In contrast, HR-TEM experiments revealed that a-MoS 3 before electrochemical tests was characterized by the random distribution of the nano-sized domains consisting of clusters of crystalline MoS 2 [22]. After the 1st full discharge, the lattice fringes were not observed and the electron diffraction showed halo pattern.…”
Section: Introductionmentioning
confidence: 87%
“…Amorphous MS 3 (M: Ti and Mo) electrode active materials are thus effective in developing all-solid-state lithium batteries with higher reversible capacity and better cyclability. In order to understand the reaction mechanisms of amorphous MS 3 electrodes in all-solid-state lithium cells, the structural changes of amorphous MS 3 during cycling tests have been examined by X-ray diffraction (XRD) measurements, Raman spectroscopy and high-resolution transmission electron microscopy (HR-TEM) [20][21][22]. In case of a-TiS 3 electrode active materials, the XRD patterns and the Raman spectra of the a-TiS 3 electrode after the first and tenth charge-discharge measurements were similar to those before the measurement [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…They showed good cycle performances in all-solid-state cells with sulfide solid electrolytes. 10,11 Among metal sulfides, iron sulfides have attracted great attention due to their cost-effectiveness and abundance in nature. FeS 2 is a typical active material for lithium cells and operation of the cells using FeS 2 as a positive electrode with organic liquid electrolytes has been reported.…”
Section: Introductionmentioning
confidence: 99%